2018
DOI: 10.1039/c7mh00958e
|View full text |Cite
|
Sign up to set email alerts
|

The progress and prospects of non-fullerene acceptors in ternary blend organic solar cells

Abstract: This review summarizes the advantages of non-fullerene acceptors and their applications in ternary blend organic solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 125 publications
(163 reference statements)
0
83
0
1
Order By: Relevance
“…The highest occupied molecular orbital (HOMO) level and the lowest unoccupied molecular orbital level of DRCN5T are −5.32 and −3.64 eV, respectively, [51] which forms an energy cascade with PTB7-Th and PC 70 BM benefiting for charge separation and collection. [29] It is observed that DRCN5T displays complementary absorption with PTB7-Th and PC 70 BM from 450 to 700 nm. Hoping to investigate the impact of DRCN5T on the absorption behaviors, the binary PTB7-Th:DRCN5T and ternary PTB7-Th:DRCN5T:PC 70 BM blend films with different DRCN5T ratio are analyzed, as shown in Figure 1d and Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The highest occupied molecular orbital (HOMO) level and the lowest unoccupied molecular orbital level of DRCN5T are −5.32 and −3.64 eV, respectively, [51] which forms an energy cascade with PTB7-Th and PC 70 BM benefiting for charge separation and collection. [29] It is observed that DRCN5T displays complementary absorption with PTB7-Th and PC 70 BM from 450 to 700 nm. Hoping to investigate the impact of DRCN5T on the absorption behaviors, the binary PTB7-Th:DRCN5T and ternary PTB7-Th:DRCN5T:PC 70 BM blend films with different DRCN5T ratio are analyzed, as shown in Figure 1d and Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 94%
“…Besides understanding the internal mechanism of binary OSCs deeply, more and more efforts were paid to improve the performance of OSCs via tuning absorption and energy level of novel donor [4][5][6][7][8][9][10][11][12] and acceptor [13][14][15] materials, optimizing processing methods, [16][17][18][19] interfacial engineering, [20] and innovative device architectures. [28][29][30] Up to now, the best performance of ternary OSCs has been reported to be over 14%. The third component is usually combined with the host single-junction system to provide complementary absorption, tune recombination behavior, and optimize the morphology of active layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such a quenched morphology is far from the binodal composition as shown in Figure 7a, and therefore its evolution toward the binodal is a spontaneous process that drives the system to a metastable equilibrium state. [73,74] This is a significant structural challenge. The aged samples also exhibited the formation of aggregation/crystals of IEICO-4F at room temperature as revealed in the GIWAXS data ( Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the V OC of P2 ternary system hardly changes with the content of NCBDT‐4Cl, which could be correlated with the cascade structure model (see Tables S1 and S2 in the Supporting Information). [ 21,53–56 ] Obviously, the P1 and P2 binary PSCs exhibit comparable device performance and P2:LA1 even shows a higher PCE than P1:LA1, which indicates that biphenyl side group could be a good candidate for constructing high performance binary PSC than phenyl side group. However, distinct device performance of P1 and P2 based ternary PSCs were observed, which could be attributed to the disturbed micromorphology induced by the extended entanglement of polymer chains.…”
Section: Resultsmentioning
confidence: 99%